ISSUES OF INFORMATION SECURITY OF IMAGES OF FOREIGN TRADE GOODS IN THE ORGANIZATION OF CUSTOMS TRANSIT (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
The article analyzes the role of images of foreign trade goods in the organization of customs control, including those obtained using Complex Inspection System (CIS). The problem of threats to the information security of the image of foreign trade goods in the chain of organization of customs control is presented. Current tasks for solving the problem have been formed and the main criteria for their implementation have been developed. Based on the results of the study, the blockchain technology is proposed as the initial mechanism for solving the problem.
Keywords: customs control; images of foreign trade goods; CIS images; trade secrets; , threat to information security; image attributes; blockchain technology